Vacuolar Proteases of Candida auris from Clades III and IV and Their Relationship with Autophagy - Daniel Clark-Flores; Alvaro Vidal-Montiel; Ricardo Mondragón-Flores; Eulogio Valentín-Gómez; César Hernández-Rodríguez; Margarita Juárez-Montiel; Lourdes Villa-Tanaca (Journal of Fungi)
Candida auris is a multidrug-resistant pathogen with a high mortality rate and widespread distribution. Additionally, it can persist on inert surfaces for extended periods, facilitating its transmissibility in hospital settings. Autophagy is a crucial cellular mechanism that enables fungal survival under adverse conditions. A fundamental part of this process is mediated by vacuolar proteases, which play an essential role in the degradation and recycling of cellular components. The present work explores the relationship between C. auris vacuolar peptidases and autophagy, aiming to establish a precedent for understanding the survival mechanisms of this emerging fungus. Thus, eight genes encoding putative vacuolar peptidases in the C. auris genomes were identified: PEP4, PRB1, PRC1, ATG42, CPS, LAP4, APE3, and DAP2. Analysis of the protein domains and their phylogenetic relationships suggests that these enzymes are orthologs of Saccharomyces cerevisiae vacuolar peptidases. Notably, both vacuolar protease gene expression and the proteolytic activity of cell-free extracts increased under nutritional stress and rapamycin. An increase in the expression of the ATG8 gene and the presence of autophagic bodies were also observed. These results suggest that proteases could play a role in yeast autophagy and survival during starvation conditions.